Theorizing the Implications of Gender Order for Sustainable Forest Management - Jeji Varghese; Maureen G. Reed (International Journal of Forestry Research)
Sustainable forest management is intended to draw attention to social, economic, and ecological dimensions. The social dimension, in particular, is intended to advance the effectiveness of institutions in accurately reflecting social values. Research demonstrates that while women bring distinctive interests and values to forest management issues, their nominal and effective participation is restricted by a gender order that marginalizes their interests and potential contributions. The purpose of this paper is to explain how gender order affects the attainment of sustainable forest management. We develop a theoretical discussion to explain how women's involvement in three different models for engagement—expert-based, stakeholder-based, and civic engagement—might be advanced or constrained. By conducting a meta-analysis of previous research conducted in Canada and internationally, we show how, in all three models, both nominal and effective participation of women is constrained by several factors including rules of entry, divisions of labour, social norms and perceptions and rules of practice, personal endowments and attributes, as well as organizational cultures. Regardless of the model for engagement, these factors are part of a masculine gender order that prevails in forestry and restricts opportunities for inclusive and sustainable forest management.